5 - Exploring Thought Leadership, Thought Liberation and Critical Consciousness for Africa’s Development - Gumede, Vusi (Africa Development, 2021)
It is argued that any discussion of Africa’s social and economic development has to take into account the three critical issues that remain pressing constraints for the further advancement of well-being in Africa: thought leadership, thought liberation and critical consciousness. These three ‘ingredients’ should anchor aspects of the socio-economic development model. As I have discussed elsewhere, the twenty-first century will most likely be remembered as the Asian century fundamentally, and secondarily as a South American century. Africa will most likely miss the twenty-first century as its own and should be putting in place what is needed to ensure that Africa indeed captures the twenty-second century. It is in this context that this article argues that thought leadership, thought liberation and critical consciousness should ensure that Africa robustly addresses whatever constraints that limit Africa’s progress. The three ‘instruments’ – the trio – should be pursued concurrently, for thought leadership without critical consciousness is useless. Thought leadership without a liberated mind is futile. Higher levels of consciousness, based on comprehensive understanding of phenomena, make for a better thought leader. It is also argued that African thought leadership must be able to produce not only a critical but also a conscious African citizenry that is grounded in pan-Africanist philosophies and driven to implement the African renaissance agenda. To do this and to successfully pursue other pertinent issues, Africa should build on its glorious past. The article also demonstrates the importance of knowledge production, its dissemination, organization and the implementation of revolutionary praxis.